Foam as a geometer - Teixeira, Paulo (2009)
Foams are found everywhere: in nature, in technology, in our home. They are examples of cellular materials: assemblies or clusters of cells (from Latin cella: a small compartment or enclosed region) packed together so that they fill space without gaps. Foams come in different kinds. Ordinary liquid foam is an experimental system that solves some difficult geometry problems.